Molino Carcarañá De Thomas Thomas Y Asociados. Su Rol En La Construcción Del Paisaje Cultural Pampeano (Santa Fe, Argentina 1875-1908) (Global Journal of Human-Social Science, 2023)
Time works, slowly or vertiginously transforms the material world through human actions and natural processes or as consequences thereof. For this reason, the understanding of the material, tangible world of human production processes allows us to access the works associated with said processes; opening up a specific and particular field of culture, of practices, with a primary purpose, which is to apprehend aspects of the historical development that originates these constructions. In this article we focus on the construction of the Pampean cultural landscape that took place in the second half of the 19th century, particularly in the Province of Santa Fe (Argentina), taking as analysis variables the railway line of the Central Argentino and the first hydraulic mill in colonia Carcarañá. Both understood as products of political decisions whose final objective was to position Argentina in the international market through the export of raw materials and their derivatives; in this particular case the flour. Thus, through a holistic analysis and taking industrial and landscape archaeology as a guide, we approached the study of a production process that characterizes the region to this day: production of raw materials of agricultural origin and the associated industry.
Keywords: cultural landscape; pampas; hydraulic mill; railway; xix century